The Deep Western Boundary Current dynamics in North Atlantic and its impact on the mean meridional overturning circulation - Talandier, Claude (HAL CCSD, 2015)
The present study tackles the Deep Western Boundary Current (DWBC) dynamics in the North Atlantic basin as its impact on the AMOC. The DWBC advects dense water masses equatorward, produced in the subpolar gyre, and is one of the major component of the Atlantic Meridional Overturning Circulation (AMOC). This circulation contributes to the northward heat transport to high latitudes and allows to stabilise climate. When computing the AMOC in different ocean general circulation models (OGCM), results cover a wide range of intensity, spatial shape and temporal variability. Such response diversity is due to several factors. One of them is the remaining uncertainty on the link between dense water formation due to convection in the subpolar gyre, which contributes to connect the AMOC upper and lower branches, and the AMOC intensity at mid-latitudes. Those uncertainties are largely due to the knowledge gap of the deep circulation in North Atlantic because its direct observation is difficult and incorrectly reproduced in ocean models with a low spatial resolution. The methodology used rely on realistic numerical simulations based on the NEMO ocean general circulation model. Three configurations with an increasing spatial resolution have been developped using the grid refinement tool AGRIF : a global grid at 1/2◦ resolution (ORCA configuration), within which a first refined grid at 1/8◦ covering the whole North Atlantic (ERNA configuration) in which a second grid at 1/32◦ over the subpolar gyre (FER configuration). Both ERNA and FER are advanced and original by two aspects; they include a Sea-Ice model within embedded grids and FER reaches a high horizontal resolution over the subpolar gyre. We study the spatial horizontal resolution impact on the mean circulation in the North Atlantic with a focus on the AMOC contrasting simulations obtained with ORCA and ERNA solutions. Increasing the resolution improves the western boundary current dynamics at surface and depth. Indeed, the DWBC transport is intensified by 8Sv in the ...